2012
DOI: 10.3109/03008207.2012.710670
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Reduces Proteoglycan Levels in Tendons

Abstract: Hyperglycemia produces a reduction in PG levels related to decreased synthesis or sulfation of glycosaminoglycans, which may contribute to the tendon pathology observed clinically in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…A biological pathway exists whereby hyperglycaemia associated with diabetes affects collagen cross-linking in tendons7 and reduces proteoglycan content 58. One previous systematic review has investigated the association between diabetes and tendinopathy 59.…”
Section: Discussionmentioning
confidence: 99%
“…A biological pathway exists whereby hyperglycaemia associated with diabetes affects collagen cross-linking in tendons7 and reduces proteoglycan content 58. One previous systematic review has investigated the association between diabetes and tendinopathy 59.…”
Section: Discussionmentioning
confidence: 99%
“…An experimental pig model evaluating patellar tendons found that proteoglycan synthesis by tenocytes was reduced in tendons exposed to high concentrations of glucose [19] . Clinically, this may explain the high rate of tendon pathology seen in patients with DM [19] .…”
Section: Impact On Soft Tissues Tendon Healingmentioning
confidence: 99%
“…An experimental pig model evaluating patellar tendons found that proteoglycan synthesis by tenocytes was reduced in tendons exposed to high concentrations of glucose [19] . Clinically, this may explain the high rate of tendon pathology seen in patients with DM [19] . A diabetic rat model of patellar tendon pathology has also demonstrated a decrease in Youngs modulus and high rate of intrasubstance failure [20] .…”
Section: Impact On Soft Tissues Tendon Healingmentioning
confidence: 99%
“…It has also been shown that the hyperglycemia could reduce proteoglycan levels in the tendon cells in high glucose condition exposure to AGEs. Decreased proteoglycan levels could increase intracellular water and cellular edema, and these alterations may lead to the increased stiffness in diabetic tendons [36].…”
Section: Biomechanical Changesmentioning
confidence: 99%
“…AGEs interact with RAGE on the cell surface and activate several critical molecular pathways including pro-oxidant events and up-regulation of inflammatory mediators; the intracellular accumulation of AGEs could lead to negative effects, such as inhibiting cell growth, destruction of nitric oxide and promoting apoptosis [52][53][54]. AGEs is also involved in the scar formation and cause of tendon cell death [36]. The tendon cells treated with high glucose concentrations showed the decreased proteoglycans and increased transforming growth factor β1 (TGF-β1) levels in an AGEindependent manner, and high TGF-β levels is reported to associate with scar formation in tendon and tenocyte death [55].…”
Section: Agesmentioning
confidence: 99%